2020
DOI: 10.1007/s10341-020-00525-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioactive Components, Antimicrobial and Antimutagenic Features of Organically and Conventionally Grown Almond Hulls

Abstract: In Turkey, almonds are grown via the following three methods: organic (O), conventional (C) and good agricultural practice (GAP). Almond seeds are mostly consumed as nuts; thus, the researchers have focused different analyses on only seeds. However, in Turkey, unripe green almond hulls are also consumed. Therefore, we studied the contents of some bioactive components, pigments, and malondialdehyde (MDA) and the antimicrobial, antioxidant, and antimutagenic activities of O, C, and GAP 'Ferradual' (Frd) and 'Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…As seen in Figures 1, 26% more phenolic compounds were detected in OHs than in CHs. Murathan et al (2020) found higher TPC in organic almond hull, similar to our study. However, in our previous study conducted on Levant hazelnuts, no difference between production systems was detected (Karaosmanoglu & Ustun, 2021).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As seen in Figures 1, 26% more phenolic compounds were detected in OHs than in CHs. Murathan et al (2020) found higher TPC in organic almond hull, similar to our study. However, in our previous study conducted on Levant hazelnuts, no difference between production systems was detected (Karaosmanoglu & Ustun, 2021).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with this study, Yang et al (2009) detected 113.7 mg CE/100 g sample TFC in hazelnut. Murathan et al (2020) reported higher levels of TFC in organic almond hull. The use of pesticides and artificial fertilizers can cause an increase in ROS (reactive oxygen species) and cause stress in the plant (Murathan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Egg yolk color is influenced by the deposition of dietary pigments such as beta-carotene, riboflavin and zeaxanthin ( Damron et al, 1984 ). Almond hulls are dried almond fruit flesh containing a high amount of chlorophyll and carotenoid contents ( Murathan et al, 2020 ). A plausible explanation of the egg yolk color difference observed here between 15% almond hull inclusion rate and control group is the pigments from almond fruit and a reduction of corn in the diets.…”
Section: Discussionmentioning
confidence: 99%